2005
DOI: 10.1002/cne.20529
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination of central nervous system proteins during the development of experimental autoimmune encephalomyelitis

Abstract: Immunization of mammals with central nervous system (CNS)-derived proteins or peptides induces experimental autoimmune encephalomyelitis (EAE), a disease resembling the human autoimmune disease multiple sclerosis (MS). Both diseases are accompanied by destruction of a part of the of the myelin sheaths, which surround neurites in the CNS. Previous studies in MS have described alterations in the citrullination of myelin basic protein, one of the main protein constituents of the myelin sheath. Here, we show that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 32 publications
3
52
0
Order By: Relevance
“…Normal white matter samples from brains of MS patients and white matter from non-neurological controls were obtained from the MS tissue bank at UCLA. Human recombinant PAD2 and PAD4 (EC 3.5-3.15) were prepared as described by Raijmakers et al 18 and supplied to us for this study. The normal mice used for this study were on the CD-1 background, and were housed in the Hospital for Sick Children Animal Care facility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal white matter samples from brains of MS patients and white matter from non-neurological controls were obtained from the MS tissue bank at UCLA. Human recombinant PAD2 and PAD4 (EC 3.5-3.15) were prepared as described by Raijmakers et al 18 and supplied to us for this study. The normal mice used for this study were on the CD-1 background, and were housed in the Hospital for Sick Children Animal Care facility.…”
Section: Methodsmentioning
confidence: 99%
“…22 The isotype-specific anti-PAD2 antibody was generated by immunization with two peptides comprising amino acids 3-18 and 516-531 of human PAD2. 18,19 The PAD4 isotype-specific antibody was raised against peptides 180-194 of human PAD4. 18 The monoclonal anticitrulline antibody, MAbF95 23 was obtained from Dr A Nicholas, Birmingham, Alabama.…”
Section: Preparation Of Myelinmentioning
confidence: 99%
“…Nervous system disorders PAD2 has been detected at high levels in the grey matter and hypothalamus [22], as well as in hippocampus, and in rat glial cells, especially astrocytes [23][24][25], microglial cells [10,25], and oligodendrocytes [26]. PAD4 has also been detected in extracts of mouse brain and spinal cord [27]. The brains of patients with multiple sclerosis (MS) show increased levels of deiminated myelin basic protein (MBP) and of deiminated glial fibrillary acidic protein (GFAP).…”
Section: Deimination In Non Cutaneous Diseasesmentioning
confidence: 99%
“…Ishigami et al [57] identified glial fibrillary acidic protein (GFAP), a marker of astrocytes in the AD brain, to be a substrate for host PAD2, and suggested a role for the citrullinated GFAP in the progression of this neurodegenerative disease. GFAP deimination was characteristic for AD in humans and in experimental autoimmune encephalomyelitis (EAE) in mice where the BBB was breached [58–60]. Although not conclusively shown, citrullinated GFAP (dysfunctional protein) would link with defects in BBB integrity because the foot processes of astrocytes tightly cover capillary openings in the endothelial cell junctions to protect neurons from extrinsic insults.…”
Section: Introductionmentioning
confidence: 99%